Acute myocardial infarction: susceptibility-weighted cardiac MRI for the detection of reperfusion haemorrhage at 1.5 T. Issue 3 (March 2016) - Durighel, G.; Tokarczuk, P.F.; Karsa, A.; Gordon, F.; Cook, S.A.; O'Regan, D.P.
Abstract : Aim: To assess whether susceptibility-weighted imaging (SWI) provides better image contrast for the detection of haemorrhagic ischaemia–reperfusion injury in the heart. Materials and methods: Thirty patients (all men; mean age 53 years) underwent cardiac magnetic resonance imaging (MRI) within 7 days of primary percutaneous intervention for acute ST elevation myocardial infarction (STEMI). Multiple gradient-echo T2* sequences with magnitude and phase reconstructions were acquired. A high-pass filtered phase map was used to create a mask for the SWI reconstructions. The difference in image contrast was assessed in those patients with microvascular obstruction. A mixed effects regression model was used to test the effect of echo time and reconstruction method on phase and contrast-to-noise ratio (CNR). Medians and interquartile ranges (IQR) are reported. Results: T2* in haemorrhagic infarcts was shorter than in non-haemorrhagic infarcts (33.5 ms [24.9–43] versus 49.9 ms [44.6–67.6]; p =0.0007). The effect of echo time on phase was significant ( p <0.0001), as was the effect of haemorrhage on phase ( p =0.0016). SWI reconstruction had a significant effect on the CNR at all echo times (echoes 1–5, p <0.0001; echo 6, p =0.01; echo 7, p =0.02). The median echo number at which haemorrhage was first visible was less for SWI compared to source images (echo 2 versus echo 5, p =0.0002). Conclusion: Cardiac SWI improves the contrast between myocardial haemorrhage and the surrounding tissue following STEMI and has potential as a new tool for identifying patients with ischaemia–reperfusion injury. Highlights: Cardiac susceptibility-weighted imaging (SWI) is feasible at 1.5T. Combining phase and modulus data allows blood products to be seen at shorter echo times. This sequence improves visualisation of reperfusion myocardial haemorrhage.